2009
DOI: 10.1097/ajp.0b013e3181a68a040
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Mechanical Pain Hypersensitivity as Sign of Central Sensitization in Unilateral Epicondylalgia

Abstract: This revealed a widespread mechanical hypersensitivity in patients with LE, which suggest that central sensitization mechanisms are involved in patients with unilateral LE. The generalized decrease in PPT levels was associated with elbow pain intensity, supporting a role of peripheral sensitization mechanisms in the initiation or maintenance of central sensitization mechanisms. In addition, females may be more prone to the development of generalized mechanical hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
3
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 46 publications
6
100
3
2
Order By: Relevance
“…In fact, previous studies have also demonstrated that individuals with either CTS or LE also have lower PPT over the tibialis anterior muscle, supporting a central sensitization process in these pain conditions. 23,28 The results from the current study are clinically relevant, as they demonstrate that a musculoskeletal pain condition such as LE exhibits similar nerve sensitization as a neuropathic pain condition like CTS. A novel finding in the current study was that, generally, pressure nerve hypersensitivity was different between patients with CTS versus LE and was related to specific nerve trunks.…”
Section: Nerve Pressure Pain Hypersensitivity and Clinical Featuresmentioning
confidence: 82%
See 4 more Smart Citations
“…In fact, previous studies have also demonstrated that individuals with either CTS or LE also have lower PPT over the tibialis anterior muscle, supporting a central sensitization process in these pain conditions. 23,28 The results from the current study are clinically relevant, as they demonstrate that a musculoskeletal pain condition such as LE exhibits similar nerve sensitization as a neuropathic pain condition like CTS. A novel finding in the current study was that, generally, pressure nerve hypersensitivity was different between patients with CTS versus LE and was related to specific nerve trunks.…”
Section: Nerve Pressure Pain Hypersensitivity and Clinical Featuresmentioning
confidence: 82%
“…25 Generalized sensitization identified by lower PPT over the median, radial, and ulnar nerve trunks has been found in patients with whiplash 57,59 and unilateral migraine, 25 suggesting possible hyperexcitability of the central nervous system. 34 It has also been shown that patients with unilateral LE 23 and unilateral CTS 28 exhibited signs of central hyperexcitability as demonstrated by lower PPT over the median, ulnar, and radial nerve trunks bilaterally when compared to healthy controls.…”
Section: Participants P Atients Diagnosed With Cts Bymentioning
confidence: 99%
See 3 more Smart Citations